2013
DOI: 10.1590/s1806-37132013000200006
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary changes on HRCT scans in nonsmoking females with COPD due to wood smoke exposure

Abstract: OBJECTIVE: To identify and characterize alterations seen on HRCT scans in nonsmoking females with COPD due to wood smoke exposure. METHODS: We evaluated 42 nonsmoking females diagnosed with wood smoke-related COPD and 31 nonsmoking controls with no history of wood smoke exposure or pulmonary disease. The participants completed a questionnaire regarding demographic data, symptoms, and environmental exposure. All of the participants underwent spirometry and HRCT of the chest. The COPD and control groups were adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
1
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 23 publications
2
23
1
2
Order By: Relevance
“…With these results, we postulated that the airflow obstruction in wood smoke COPD is mainly caused by severe airway involvement rather than by a loss of elastic recoil due to emphysema. Similar to our results, a recent study from Brazil [4] showed that the most common findings on CT scans in a wood smoke-exposed COPD group were bronchial wall thickening (66.7%), bronchiectasis (54.8%), mosaic perfusion pattern (45.2%), parenchymal bands, tree-in-bud pattern and laminar atelectasis (p,0.001 versus the control group for all) and, in contrast, emphysema was uncommon. The authors described a positive association between bronchial wall thickening and hour-years of wood smoke exposure [4].…”
supporting
confidence: 91%
See 2 more Smart Citations
“…With these results, we postulated that the airflow obstruction in wood smoke COPD is mainly caused by severe airway involvement rather than by a loss of elastic recoil due to emphysema. Similar to our results, a recent study from Brazil [4] showed that the most common findings on CT scans in a wood smoke-exposed COPD group were bronchial wall thickening (66.7%), bronchiectasis (54.8%), mosaic perfusion pattern (45.2%), parenchymal bands, tree-in-bud pattern and laminar atelectasis (p,0.001 versus the control group for all) and, in contrast, emphysema was uncommon. The authors described a positive association between bronchial wall thickening and hour-years of wood smoke exposure [4].…”
supporting
confidence: 91%
“…Finally, the authors concluded that this is the first study showing differences in chronic obstructive pulmonary disease (COPD) phenotypes in living women with biomass-versus tobaccosmoke exposure [1]. However, there have been previous studies investigating the differences in clinical presentation, pulmonary function tests and CT scan findings between COPD related to wood smoke and tobacco smoke [2][3][4][5]. In 2008, a review by TORRES-DUQUE et al…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Gupta and Shah [10] in their review on BAF observed that 632/792 (79.8%) patients with BAF were females. The mean exposure index in 42 non-smoking females with COPD from Brazil [12] was 209.1 ± 98.4 hour-years. A multivariate analysis from India [13] calculated that minimum threshold of exposure index of 60 hour-years was a significant risk factor for occurrence of chronic bronchitis in women.…”
Section: Discussionmentioning
confidence: 97%
“…Sin embargo, existen algunas diferencias entre las característi-cas de la EPOC por humo de biomasa y por humo de tabaco 53-60 (tabla 1). A nivel histopatológico, por ejemplo, los pacientes con EPOC por humo de biomasa presentan un fenotipo con más bronquiolitis, con más antracosis y fibrosis pulmonar, así como mayor engrosamiento de la pared arterial que los pacientes con EPOC fumadores, cuyo fenotipo presentaría un mayor enfisema pulmonar 55,[57][58][59] . En este sentido, un trabajo reciente desarrollado por Krimmer et al 61 ha puesto de manifiesto que fibroblastos en cultivo expuestos a humo de biomasa incrementan su producción de fibronectina.…”
Section: Mecanismos Patogénicos Del Humo De Biomasa En La Enfermedad unclassified